Digital Heritage and Its Implications for Global Citizenship Education - Ahmed, Amira; Dulic, Aleksandra (Mimesis Journal, 2024)
Digital media technologies provide endless possibilities for disseminating and preserving cultural heritage, opening new avenues to intercultural exchange. Digital-heritage applications have the potential to bring global communities together by providing creative opportunities for cultural exchange and enabling diverse forms of interactions in a culturally specific context of digital-heritage representations. The article presents an immersive experience based on Egyptian heritage developed in a multidisciplinary graduate specialization program at the University of British Columbia Okanagan, Canada. We propose using an educommunication approach to heritage in which students and teachers act as partners to explore new ways of transformative cultural-learning experiences to contribute to intercultural exchanges as implications of global citizenship education (GCED). We investigate how integrating digital-heritage experiences in citizenship education and collaborative student-centered instructional design can promote GCED and enhance intercultural dialogue in university classrooms. Finally, this article aims to fill the gap in the limited literature that connects heritage education and global citizenship and advance the understanding of the implications of virtual reality and interactive 3D-multimedia in taking forward GCED’s mission of promoting intercultural communication, open-mindedness, mutual understanding, and respect.